2016
DOI: 10.18805/ijar.v0i0f.3791
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and anti-fungal susceptibility pattern of dermatophytes isolated from dogs, cats and pet owners in and around Kolkata, India

Abstract: Pet animals mostly suffer from dermatophytic infections and these animals can easily transmit the infection to their handlers or pet owners. Study of 362 clinically suspected cases of dermatophytic infections collected mainly from dogs (n=123), cats (n=202) and few pet owners (n=37) in and around Kolkata, was conducted to detect a total of 285 (78.7%) samples to be positive for significant dermatophytic fungal infections, with cats to be the highest in prevalence (55.4%) followed by dogs (37.9%) and human bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Many epidemiological studies have shown that T. mentagrophytes is globally distributed, and is one of the most frequent or common pathogens of fungal skin disease [ 5 , 6 , 7 , 8 ]. Some animals, including rabbits, foxes, minks, cats, and dogs are the natural hosts of T. mentagrophytes , which causes skin diseases in these animals and affects their fur quality [ 9 , 10 ]. In cases of low immunity or a damaged skin barrier, close contact with the above-mentioned sick animals can easily result in fungal skin diseases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many epidemiological studies have shown that T. mentagrophytes is globally distributed, and is one of the most frequent or common pathogens of fungal skin disease [ 5 , 6 , 7 , 8 ]. Some animals, including rabbits, foxes, minks, cats, and dogs are the natural hosts of T. mentagrophytes , which causes skin diseases in these animals and affects their fur quality [ 9 , 10 ]. In cases of low immunity or a damaged skin barrier, close contact with the above-mentioned sick animals can easily result in fungal skin diseases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%